Level Berpikir Visual Pada Komunikasi Matematis Siswa - fendiyanto, fendiyanto; Susanti, Elly; Nafisatul Qur'ani, Fauziyah; Bahasa Indonesia, Bahasa Indonesia (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2024)
This study is motivated by the lack of previous researchers examining the level of visual thinking in students' mathematical communication. This research aims to describe the level of visual thinking in students' mathematical communication. The research method is literature research or literature review (literature review, literature research). Research activities were carried out in a structured way through the stages of data collection, data reduction, data display, discussion to conclusion. Technically, the research steps were carried out as follows: 1) the preparation stage, determining the fixed and dependent variables, determining the data to be analysed and selecting articles that are in accordance with the variables in the title, 2) the implementation stage, searching and collecting articles, taking the results of the articles obtained, and 3) the data analysis stage, this stage is used to determine the level of visual thinking and indicators of students' mathematical communication which will be useful to determine the level of visual thinking of students' mathematical communication. The results showed that there is a relationship between the level of visual thinking and students' mathematical communication, so that the levels of visual thinking in mathematical communication are: Non Visual Level, Local Visual Level, and Global Visual Level.